The impact of vegetation cover loss on land surface temperature in the small island of Sabang City: Implication for sustainable spatial planning - Naja Asrina; Eldina Fatimah; Ashfa Achmad (International Journal of Disaster Management, 2025)
Sabang City has undergone ongoing development and changes in spatial patterns, leading to significant transformations in land use and land cover (LULC), particularly a reduction in vegetation and forest areas. These changes have contributed to a rise in land surface temperatures (LST). This study analyzed the spatial and temporal impacts of these changes on LST and vegetation health using the Normalized Difference Vegetation Index (NDVI) based on Landsat 8 imagery data from 2013 and 2023. Over the decade, forest cover declined by 11.65% (2,639.96 ha), while agricultural and built-up areas increased by 15.82% and 5.57%, respectively. LST in built-up areas rose by 0.7C, while vegetated areas experienced a 1.1C temperature decrease, highlighting the role of vegetation in local climate regulation. NDVI analysis revealed a 5% decrease in high-density vegetation areas and an increase in low vegetation zones, supporting a negative correlation between NDVI and LST. Areas with less vegetation exhibited higher temperatures. These findings emphasize the need to integrate vegetation and surface temperature indicators into spatial planning. Preserving vegetative cover is essential for mitigating climate risks such as drought and forest fires. This study provides evidence-based guidance for sustainable development and disaster risk reduction in small island cities like Sabang.